Crab-Eating Mongoose Herpestes urva: Occurrence and its Activity in Mid-Hills of Nepal - Sharma, Hari Prasad; Adhikari, Binaya; Bhandari, Shivish; Baral, Kedar; Kunwar, Ripu Mardhan (Journal of Institute of Science and Technology, 2021)
Small carnivores are able to adapt to patchy forests and human dominated landscape in proximity to water sources. Small carnivore’s population is declining due to anthropogenic effects, and in most of the areas, their occurrence is little known. We aimed to identify the spatial occurrence of crab-eating mongoose, the factors affecting the occurrence of species and coexistence with other species using camera trap. The crab-eating mongoose mostly preferred the shrub-land habitat (65%) and followed by agriculture land, forest and grassland. Almost all preferred habitats were near to water sources. The occurrence of crab-eating mongoose was influenced by human disturbances. Their occurrences were decreased with increasing disturbances. In addition, the crab-eating mongoose’s occurrence was also decreased with increasing distance to water sources. The movement activities of crab-eating mongoose were varied according to time period (F = 6; df = 14; p < 0.013), and was mostly active at day to mid-night (16.00 to 12.00 hours) and mid-night to early morning (12.00 to 8.00 hours). The crab-eating mongoose co-exists with other carnivores including Leopard, Jungle cat, Masked-palm civet, Small Indian mongoose, Leopard cat, Yellow-throated martin, and Large Indian civet. In addition, its occurrence was affected by human interference. The data available from this study can be used to develop site/species-specific conservation plans that aid stewardship for biodiversity conservation.